2005
DOI: 10.1128/aac.49.4.1447-1454.2005
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and In Vivo Activities of Macrolide Derivatives against Mycobacterium tuberculosis

Abstract: Existing macrolides have never shown definitive clinical efficacy in tuberculosis. Recent reports suggest that ribosome methylation is involved in macrolide resistance in Mycobacterium tuberculosis, a mechanism that newer macrolides have been designed to overcome in gram-positive bacteria. Therefore, selected macrolides and ketolides (descladinose) with substitutions at positions 9, 11,12, and 6 were assessed for activity against M. tuberculosis, and those with MICs of <4 M were evaluated for cytotoxicity to V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
250
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 202 publications
(252 citation statements)
references
References 26 publications
1
250
0
1
Order By: Relevance
“…To provide further proof-of-principle data to support the notion that specific inhibitors of mPTPB may be effective antiTB agents, we tested I-A09 against the classical Mtb Erdman strain in a model of active TB infection performed in a mouse macrophage J774A.1 cell line (32). Cultures of macrophages infected with actively growing Mtb were treated with 10 ÎŒM I-A09 starting on Day 0 and the cultures were allowed to incubate for a further seven days before assessment of the remaining bacterial load in the cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To provide further proof-of-principle data to support the notion that specific inhibitors of mPTPB may be effective antiTB agents, we tested I-A09 against the classical Mtb Erdman strain in a model of active TB infection performed in a mouse macrophage J774A.1 cell line (32). Cultures of macrophages infected with actively growing Mtb were treated with 10 ÎŒM I-A09 starting on Day 0 and the cultures were allowed to incubate for a further seven days before assessment of the remaining bacterial load in the cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Inhibition of growth of M. tuberculosis Erdman (ATCC 35801) in a macrophage cell culture was assessed as previously described (32). J774A.1 cells were grown to confluency in 75 cm 2 cell culture flasks in DMEM medium containing 10% FBS.…”
Section: Methodsmentioning
confidence: 99%
“…As expected, the evaluation of MBCs against Mtb H 37 Rv (Table 2) showed that the 6-hydrogenquinolones, like clinical FQs, are bactericidal and kill Mtb at concentrations close to those that cause inhibition. Finally, all the compounds resulted to be not toxic against Vero cells (26) at the concentration tested of 102 lM.…”
Section: Mycobacterium Tuberculosis Inhibitory Activitymentioning
confidence: 99%
“…Similarly, cytotoxicities were determined on Vero cells according to a published procedure (26). The MBC was determined for Mtb H 37 Rv by subculturing onto a drug-free solid medium and counting of CFU following exposure in Middlebrook 7H9 medium supplemented with drug concentrations equivalent to and higher than the previously determined MICs against the same strains.…”
Section: Biologic Evaluationmentioning
confidence: 99%
“…Substitutions of C1401A/T or G1483T led to kanamycin resistance (6). Mycobacteria belonging to M. tuberculosis complex have intrinsic resistance to macrolides (7,8). The resistance has been attributed to erm genes, which are 23 S rRNA methyltransferases (9).…”
mentioning
confidence: 99%